Exercise Dependence and Body Image Concerns Amongst Group Fitness Instructors: A Self-Determination Theory Approach - Reinboth, Michael S.; Sundgot-Borgen, Jorunn; Bratland-Sanda, Solfrid (Frontiers in Psychology, 2022)
Despite that group fitness instructors serve as significant role models with potentially great impact on class participants’ motivation for exercise, they as a group are highly understudied. The aim of this study was therefore to examine group fitness instructors’ motivational regulations for exercise, and how these motivational regulations can predict symptoms of exercise dependence and body image concerns. Methods: Group fitness instructors from the largest fitness companies in Norway (n=837, response rate: 57%) completed an online survey with Situational Motivation Scale (SIMS), Exercise Dependence Scale (EDS), Eating Disorders Inventory subscales drive for thinness (EDI-DT) and body dissatisfaction (EDI-BD), and weekly amount of exercise and instruction. Results: The instructors scored very high on Identified regulation and Intrinsic Motivation for exercise. EDS total score was positively correlated with all SIMS subscales and weekly instruction was positively correlated with Intrinsic Motivation. Multiple hierarchical regression analyses found both self-determined motivational regulations as well as external regulation to positively predict EDS score. External regulation positively predicted EDI-DT, and EDI-BD. Discussion: Group fitness instructors seem highly intrinsically motivated for exercise, which is hypothesized to have a positive impact on group fitness class participants. High self-determined exercise behavior does not seem to buffer against symptoms of exercise dependence in this special population. There is a need for awareness of group fitness instructors who show high exercise dependency scores due to the link to body image concerns, amotivation and external regulated motivation. Keywords: group fitness instructors, motivational regulations, exercise dependence